Age Distribution and Concomitant Injuries in Pulmonary Contusion: An Analysis Based on Routine Data - Finkbeiner, Rebekka; Krinner, Sebastian; Langenbach, Andreas; Besendörfer, Manuel; Schulz-Drost, Stefan (Thoracic and Cardiovascular Surgeon, 2018)
BACKGROUND: As the population ages, low-energy thoracic injuries are becoming increasingly relevant in individual injuries, particularly pulmonary contusions (PCs) and their common concomitant injuries. The objective of this study was to determine the prevalence and age distribution of thoracic trauma, especially PC, to make conclusions about common secondary diagnoses and developments in management. METHODS: A retrospective analysis of 209,820 cases, based on German routine data from the years 2009 to 2015, with a main diagnosis (MD) or secondary diagnosis (SD) of thoracic trauma (S27 according to ICD-10) was performed. The entire patient collective with a MD of S27 was examined as well as those with PCs (S27.31). RESULTS: In all 61,016 patients with a MD of S27, 7,558 (12.4%) had a MD of PC and among the 148,804 patients with a SD of S27, 58,247 patients (39.1%) had a SD of PC. PC occurs mostly in the age groups of 20 to 25, 45 to 50, and 70 to 75 years. The proportion of older people tends to be increasing. The most concomitant thoracic injuries were serial rib fractures (27.1%), pneumothorax (11.9%), and sternum fractures (6.2%). Computed tomography scan is the most common diagnostic tool in PC (MD >80%, SD >60%). Therapeutically, intensive care (>50%) and chest drainage are most important (MD: 12.5%, SD: 60.1%), while operative measures are rare (≤ 4%). CONCLUSION: PC shows a marked increase in the incidence, especially in older patients and as a companion diagnosis in thoracic injuries. It should be diagnosed early as well as its concomitant injuries to avoid complications.
EVALuna2:35788